The determination of airborne fungal flora of two different hospitals in Istanbul (Turkey) - (:unkn) unknown (My University, 2011)
The current study was carried out on monthly fungal flora of Marmara University Hospital and Goztepe Education and Research Hospital in Istanbul between 2005 and 2006. The Petri-plate method based on gravity was used for isolation. A total of 175 fungal colonies were isolated from Marmara University Hospital and the maximum isolation was in May and the minimum isolation was in February. Species isolated from Marmara University Hospital; are Cladosporium (42.9%), Alternaria (18.9%), Penicillium (12.6%), Aureobasidium (11.4%), Aspergillus (6.9%), Mycelia Sterilia (4.6%), Scopulariopsis (1.7%), Rhizopus (0.6%) and Ulocladium (0.6%). A total of 182 fungal colonies were isolated in Goztepe Education and Research Hospital and the maximum isolation was in May and the minimum isolation was in January. Isolated species are; Cladosporium (32.4%), Alternaria (24.2%), Penicillium (15.9%), Aureobasidium (9.3%), Aspergillus (7.1%), Scopulariopsis (3.8%), Ulocladium (3.3%), Mycelia Sterilia (2.7%), Rhizopus (0.5%) and Paecilomyces (0.5%). A number of fungal species with pathogenic potential were encountered among the species isolated in this study. The results obtained from the species distribution showed that there were no differences between the two hospitals.
Keywords: Airborne Fungi; Hospital Air; Indoor Air; Mould; Mould Flora